Dampak Customer Relationship Management (CRM) Dan Brand Ambassador Terhadap Loyalitas Konsumen Ms Glow Men - Raihan Wishal Nafis; Andi Ismail Marasabessy (Fakultas Ekonomi Universitas Panca Marga, 2022)
Today, it is no longer taboo that many Indonesian people, especially men, are starting to pay attention to the condition of their appearance. This is what ultimately encourages many cosmetic company to produced specific product for men who are very concerned about their appearance. This study aims to determine the effect of Customer Relationship Management (CRM) and Brand Ambassador on MS Glow Men consumer loyalty with a total sample of 110 respondents. The results showed that Customer Relationship Management (CRM) had a significant positive effect on Loyalty by 21.3% and Brand Ambassador had a significant positive effect on Loyalty by 58.9%. Keywords: Customer Relationship Management, Brand Ambassador, Loyalty